2020
DOI: 10.1038/s41385-019-0238-1
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic-induced microbiome perturbations are associated with significant alterations to colonic mucosal immunity in rhesus macaques

Abstract: The diverse bacterial communities that colonize the gastrointestinal tract play an essential role in maintaining immune homeostasis through the production of critical metabolites such as short chain fatty acids (SCFA), and this can be disrupted by antibiotic use. However, few studies have addressed the effects of specific antibiotics longitudinally on the microbiome and immunity. We evaluated the effects of four specific antibiotics; enrofloxacin, cephalexin, paromomycin, and clindamycin; in healthy female rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 59 publications
3
21
0
1
Order By: Relevance
“…Similarly, we also observed relatively decreased levels of C 2 , C 3 , C 5 , and C 6 VFAs of test groups ( Figure 5 A,B,D,E), which may be led by the considerably reduced OD values ( p < 0.05) after anaerobic incubation of antibiotic-treated cultures for six hours. Among the studied VFAs, C 4 VFA such as butyric acid has received an increased attention because of its beneficial effects on the gut as a key energy source for colonic epithelial cells [ 26 ]. It was also reported to exert various intestinal activities that are involved in modulating intestinal epithelial defense and improving inflammation and intestinal motility [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, we also observed relatively decreased levels of C 2 , C 3 , C 5 , and C 6 VFAs of test groups ( Figure 5 A,B,D,E), which may be led by the considerably reduced OD values ( p < 0.05) after anaerobic incubation of antibiotic-treated cultures for six hours. Among the studied VFAs, C 4 VFA such as butyric acid has received an increased attention because of its beneficial effects on the gut as a key energy source for colonic epithelial cells [ 26 ]. It was also reported to exert various intestinal activities that are involved in modulating intestinal epithelial defense and improving inflammation and intestinal motility [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the extrinsic factors, such as diet and antibiotics, perturbate the gut microbiome community and their metabolites, which may lead to dysbiosis [ 17 , 25 ]. The administration of antibiotics has been widely applied in the treatment and prevention of infectious diseases [ 26 ]. However, fewer studies have been conducted to evaluate the effect of antibiotics on the VFA profiles of the gut microbiota [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…infection have advanced the understanding of gut-driven systemic immune activation and HIV disease progression [24]. The microbiome is in uenced by numerous factors such as age, environment, food and antibiotics [25][26][27][28][29]. With regard to the liver during SIV infection, prior studies have identi ed elevated bacterial loads during SIV infection [30,31], as well as in the context of cART [32], and have shown that bacteria may increase immune cell in ltration [30].…”
Section: Understanding Of the Gut Microbiome And Immune Changes Durinmentioning
confidence: 99%
“…Fecal microbiome largely represent the last stage of transitions of microbial communities along the GI tract, and as numerous biogeographical analyses revealed the distinction of fecal microbiome from different GI sections 2 , where important biological processes take place. Largely composed of bacteria and archaea from lumen (content), fecal microbiome also indicate poorly on the mucosal microbiome, community at the intimate interface of cross-talk with the host and especially interactions with immune systems 3, 4 . In addition, continual fecal samples are rarely taken within short intervals but mostly daily due to human physiology, which disables investigations into community dynamics with finer resolution, for instance diurnal cycles that are feasible in mouse and have already been shown to be closely linked to host physiological homeostasis 5, 6, 7 .…”
Section: Introductionmentioning
confidence: 99%